2020
DOI: 10.1519/jsc.0000000000002910
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Changes From Traditional vs. Ultra–Short-Term Recordings in Relation to Preseason Training Load and Performance in Futsal Players

Abstract: Nakamura, FY, Antunes, P, Nunes, C, Costa, JA, Esco, MR, and Travassos, B. Heart rate variability changes from traditional vs. ultra–short-term recordings in relation to preseason training load and performance in futsal players. J Strength Cond Res 34(10): 2974–2981, 2020—The aims of this study were to analyze heart rate variability (HRV) changes in futsal players during preseason training using both “criterion” (10-minute) and ultra-shortened (2-minute) measures, and to determine whether they were related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 28 publications
4
51
0
3
Order By: Relevance
“…The paradoxical relationship between LnRMSSD mean and LnRMSSD cv provides a true measurement of autonomic adaptation to sports training and avoids the misinterpretation of daily fluctuation of vagal-related changes and psychometric status [44]. Nakamura et al [37] recently reported that increase in ultra-short-term records of LnRMSSD mean and decrease in LnRSSMD cv were associated with improving performance of Yo-Yo intermittent recovery level 1 test after 4 weeks preseason training in Portuguese professional futsal players. Nakamura et al recorded the LnRMSSD 3 times per week, whilst our study recorded daily morning of resting LnRMSSD through the training camps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paradoxical relationship between LnRMSSD mean and LnRMSSD cv provides a true measurement of autonomic adaptation to sports training and avoids the misinterpretation of daily fluctuation of vagal-related changes and psychometric status [44]. Nakamura et al [37] recently reported that increase in ultra-short-term records of LnRMSSD mean and decrease in LnRSSMD cv were associated with improving performance of Yo-Yo intermittent recovery level 1 test after 4 weeks preseason training in Portuguese professional futsal players. Nakamura et al recorded the LnRMSSD 3 times per week, whilst our study recorded daily morning of resting LnRMSSD through the training camps.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive data of the measured variables are presented as mean ± standard deviation (SD) and 90% confidence intervals (90% CI). The intra-subject coefficient of variation of LnRMSSD during each study period was used to calculate the LnRMSSD cv [37]. Between training camps/tournament differences of ultra-short-term and short-term LnRMSSD were analyzed by using the standardized differences of the effect size (ES).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vagal indices of HRV, such as the logarithm of the root mean square of successive R-R interval differences (lnRMSSD), reflecting cardiac parasympathetic modulation, are sensitive to fatigue and have been useful in evaluating individual training adaptation in soccer players [32, 33]. Furthermore, the weekly (4-7 days) CV of lnRMSSD (lnRMSSD CV ) may provide valuable information concerning training-induced perturbations in homeostasis, i.e., can reflect the day-to-day variations in cardiac parasympathetic activity [32, 34, 35]. In general, athletes with a lower lnRMSSD CV are more aerobically fit and seem to cope better with training and match loads [3638].…”
Section: Introductionmentioning
confidence: 99%
“…Markers of cardiac-autonomic function such as resting heart rate (RHR) and its variability (HRV) are objective, non-invasive physiological markers that can be easily obtained with mobile devices [11], and represent convenient indicators of cardiovascular recovery status [12]. Athletes who demonstrate progressive increases in HRV throughout preseason training in other football codes generally exhibit positive adaptations such as a reduced HRex and increased aerobic fitness [13][14][15][16]. However, excessive loads during training camps may lead to overreaching, causing decrements in HRV, baroreceptor sensitivity, subjective wellbeing, and performance capacity [17].…”
Section: Introductionmentioning
confidence: 99%